Peran Internasional Criminal Court dan Kejahatan Terhadap Kemanusiaan Oleh Militer - Sulistia, Teguh (Indonesian Journal of International Law, 2007)
Human rights violations become an interesting topic in this 21st century along with emerging respects for civil rights for every violent action. Every person has freedom from persecution and violence either by militia or military force. This can be seen from the establishment of the International Criminal Court (ICC) to prosecute war crimes and crimes against humanity. These efforts are aimed to those who are violating human rights especially by the military force which they can be brought the ICC for their actions.